Perlindungan Hukum terhadap Konsumen dalam Transaksi Jual Beli Properti dengan Sistem Pre-Project Selling Ditinjau Berdasarkan Hukum Positif di Indonesia: (Studi Kasus PT Hadez Graha Utama) - Shaleemar Nandita Lilawanti; Etty Mulyati; Agus Suwandono (Jurnal Hukum Lex Generalis, 2024)
The increase in the buying and selling of residential properties has led to intense competition between developers, who are trying to sell quickly with the use of the pre-project selling system. However, this system has a high risk for consumers, as happened in the sealing of Jatiasih Central City housing unit with PT Hadez Graha Utama as a developer who built housing illegally and resulting on harm to 260 consumers. Therefore, legal protection is required for consumers who are harmed both internally and externally. Based on Law No. 8 of 1999 concerning Consumer Protection and Law No.1 of 2011 concerning Housing and Residential Areas, consumers can file a Class Action lawsuit to the court demanding PT Hadez Graha Utama to be responsible for default and unlawful acts (PMH).